Perceived Environmental Uncertainty, Management Acounting Infor-mation Systems and Decentralization - Kirmizi Ritonga (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2009)
This study examines the effect of perceived environmental uncertainty (PEU) on the design of management accounting information system (MAIS) which is moderated by decen-tralization. MAIS is designed to provide chief executive officers information to make decision, planning, and controlling which was defined in terms of the extent to which managers use time information characteristics of broad scope, timeliness, and aggregation in manufactur-ing firms. The study involved 158 chief executive officers that have been responsible for an organization, drawn from the manufacturing companies in Jakarta, Tangerang, Bogor, and Karawang. The questionnaire survey, which was analyzed by using a regression analysis, suggests that PEU have an effect on the aggregated MAS information moderated by decen-tralization.Keywords: PEU, MAIS, Manufacturing Companies, Decentralization